The influencing machine : Brooke Gladstone on the media - Gladstone, Brooke; Neufeld, Josh; Jones, Randy, 1950-; Jones, Susann (New York, NY : W.W. Norton, 2012)
The cartoon of Brooke Gladstone conducts the reader through two millennia of history-from the newspapers in Caesar's Rome to the penny press of the American Revolution and the manipulations of contemporary journalism. Gladstone's manifesto debunks the notion that "The Media" is an external force, outside of our control, since we've begun directly constructing, filtering, and responding to what we watch and read. With fascinating digressions, sobering anecdotes, and brave analytical wit, The Influencing Machine equips us to be smart, savvy, informed consumers and shapers of the media. It shows that we have met the media and it is us
In the beginning -- The American exception -- Existential angst -- Canis journalisticus -- Birds on a wire -- News you can't use -- The great refusal -- Bias -- War -- Objectivity -- Disclosure -- The matrix in me -- The influencing machines -- Um, panic? -- I, robot -- I media
Includes bibliographical references (p. 163-170) and index
Keywords: Gladstone, Brooke -- Comic books, strips, etc; Journalism -- Comic books, strips, etc; Broadcast journalism -- Comic books, strips, etc